Lepusigobius, a new generic name proposed for Gobiosoma pallida Herre, 1934 (Gobiiformes: Gobiidae) from west Pacific with re-description of the species - Suzuki, Toshiyuki; Li, Hsien-En; Chen, I-Shiung (Zootaxa, 2025)
In this study, after examining new additional materials and data collected from type materials, we designate a new gobiid genus, Lepusigobius, for Gobiosoma pallida Herre, 1934, a species that has a perplexing taxonomic history. Lepusigobius can be initially characterized by having a reduced transverse neuromast organ arrangement, a rabbit-like notched upper lip, and a dorsal pterygiophore formula of 3-12210. Other morphological diagnostic characters of Lepusigobius include the body moderately elongated, totally naked, pelvic fins with fully developed connecting membrane and frenum, and both dorsal fins connected basally. Descriptions of head lateral line system configurations and both fresh and preserved colourations are given, and a comprehensive comparison of Lepusigobius with other related genera are also provided herein.